STUDI TENTANG PERILAKU NARSISME PADA PESERTA DIDIK KELAS VIII SMP NEGERI 1 NANGA MAHAP - Meldawati, Heni; Asrori, H.M.; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to analyze and describe the narcissistic behavior ofClass VIII students of SMP Negeri 1 Nanga Mahap in 2022. Theproblem of this research is: "What is the narcissistic behavior of ClassVIII students of SMP Negeri 1 Nanga Mahap in 2022?" The researchmethod used is descriptive method in the form of survey research. Theresearch population is 128 people, with a research sample of 45 people.The data collection technique uses indirect communication techniqueswith the Narcissism Behavior Inventory data collection tool. Dataanalysis technique using percentage analysis. The results of the studyshow that: (1) Overall the narcissistic behavior of Class VIII studentsof SMP Negeri 1 Nanga Mahap in 2022 is in the "high" category. (2)Internal factors of narcissistic behavior in students achieve results of73% in the high category, namely psychological and biological factors,while external factors that cause narcissistic behavior in studentsachieve results of 72% also include in the high category, namelysociological factors or social environmental factors. . (3) The impactof narcissistic behavior on students achieves a result of 72% with ahigh category so that it can have a negative impact on students. (4)Efforts that have been made by guidance and counseling teachers haveprovided information services to students about narcissistic behaviorand its various negative impacts.